Respuesta :

Answer:

x = 19, 17

Step-by-step explanation:

(x-18)(x-18)=1

x^2 - 36x + 324=1

x^2 - 36x = -323

x^2 - 36x + 323 = 1

(x-19)(x-17) = 0

x = 19, 17

Answer: x = 17,19

Step-by-step explanation:

Method 1: Solve by Equations

The most common method, so...

[tex](x-18)^2=1[/tex]

[tex]x^2-2x(18)+18^2=1[/tex]

[tex]x^2-36x+324=1[/tex]

Move 1 to the left.

[tex]x^2-36x+324-1=0\\x^2-36x+323=0[/tex]

[tex](x-17)(x-19)=0\\x=17,19[/tex]

The value of x are 17 and 19.

Method 2: Solve by Graphing

I don't recommend this method since you might be bad at graphing (You must be perfect at graphing)

So given [tex](x-18)^2=1[/tex]

Move 1 to the left

[tex](x-18)^2-1=0[/tex]

Change 0 to y

[tex]y=(x-18)^2-1[/tex] The vertex is at (18,-1)

Draw the graph (Parabola)

When you finish drawing the graph, x-intercepts should be around 17 and 19

x-intercepts are the value of x so if x-intercepts are at (17,0) and (19,0) then the value of x are both 17 and 19